2003
DOI: 10.1007/bf02492405
|View full text |Cite
|
Sign up to set email alerts
|

Determination of binding constants between the antibiotic ristocetin A and D-Ala-D-Ala terminus peptides by affinity capillary electrophoresis

Abstract: SummaryBinding constants belween the antibiotic ristocetin A (Rist A) and D-Ala-D-Ala terminus peptides were determined using affinity capillary electrophoresis (ACE). In these experiments ~o techniques are used to obtain binding constants. In the first, a plug of RistAand non-interacting standards are injected and electrophoresed. Analysis of the change in the relative migration time ratio (RMTR) of Rist, relative to the non-interacting standards, as a function of the concentration of peptide, yields a value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Table 1 summarizes the binding data obtained for the binding of glycopeptides to D-Ala-D-Ala terminus peptides. The values for K b obtained by the oncolumn ligand derivatization technique are comparable to those observed using standard ACE techniques [16,19].…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Table 1 summarizes the binding data obtained for the binding of glycopeptides to D-Ala-D-Ala terminus peptides. The values for K b obtained by the oncolumn ligand derivatization technique are comparable to those observed using standard ACE techniques [16,19].…”
Section: Resultssupporting
confidence: 69%
“…During the past decade affinity capillary electrophoresis (ACE) has emerged as a useful and sensitive technique for studying bimolecular noncovalent interactions and for determining binding and dissociation constants of formed complexes [15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32]. ACE uses the resolving power of CE to distinguish between the free and bound forms of a receptor as a function of the concentration of free ligand.…”
Section: Introductionmentioning
confidence: 99%
“…In this technique, four separate plugs of sample are introduced into the capillary and electrophoresed. [106], ristocetin A [107], and their on-column modified derivatives [56]. Several other applications of CAE for the investigation of the interactions of glycopeptide antibiotics, vancomycin, ristocetin and their derivatives, with peptides that mimic the bacterial cell wall binding site can be found in the survey [108].…”
Section: Affinity Electrophoresismentioning
confidence: 98%
“…CAE is now widely used for the determination of association or dissociation constants of peptide complexes with both low-and high-molecular-mass ligands. Several studies have been performed to estimate receptor-ligand interactions using a model system consisting of glycopeptide macrocyclic antibiotic vancomycin from Streptomyces orientalis and free or derivatized dipeptide D-Ala-D-Ala [55,106,107]. CE techniques are frequently applied to the quantitative investigation of peptide interactions with other peptides, proteins, nucleic acids or other ligands.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…Calculations indicated that the binding constants of peptides show considerable differences. The affinity CE method has been proposed for the determination of other molecular interactions (Azad et al, 2003).…”
Section: Peptidesmentioning
confidence: 99%